KINERJA PEGAWAI DAN REALISASI PENDAPATAN PAJAK PADA BADAN PENGELOAAN PENDAPATAN DAERAH KOTA BANDUNG - Ade Sudrajat (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
Employee performance is a very important instrument and as a barometer in an organization to get an assessment of whether the organization is forward or backward. Employee performance is also determined by the quantity, quality, performance of human resources in the organization, because human resources are a very decisive factor in running an organization. The Regional Revenue Management Agency of the City of Bandung has sufficient quality human resources to be able to improve performance from time to time, so that the tax target and realization from year to year can be increased in accordance with the existing potential.